Drug-Induced Liver Injury: Role of Circulating Liver-Specific microRNAs and Keratin-18 - Romilda Cardin; Debora Bizzaro; Francesco Paolo Russo; Francesca D’Arcangelo; Francesco Ideo; Filippo Pelizzaro; Chiara Carlotto; Milena Minotto; Fabio Farinati; Patrizia Burra; Giacomo Germani (Gastroenterology Insights)
Background and Objective: Drug-induced liver injury (DILI) is increasingly becoming a cause of acute hepatitis. The study evaluated the role of liver-specific microRNAs (miRNAs) and keratin-18 (K-18) markers M30 (apoptosis) and M65 (necrosis) as biomarkers of acute hepatitis. Methods: Sixty-eight patients were sub-grouped as DILI, HBV- and alcohol-related acute hepatitis. Five healthy controls were included. The expression of plasma miR-21-5p, miR-34a-5p and miR-122-5p was evaluated by RT-qPCR analysis using healthy volunteers as reference. M30 and M65 were determined with ELISA kits. Results: All markers were significantly higher in the acute liver disease patients compared to controls. In DILI, miRNA levels positively correlated with M30, M65 and ALT. miR-122-5p had the highest AUC of 0.73, sensitivity of 76.2 and specificity of 72.2 in identifying DILI from other groups. Patients with hepatocellular-pattern DILI showed higher miR-122-5p and miR-21-5p compared to patients with cholestatic or mixed pattern. A new score to discriminate DILI versus other causes of acute hepatitis was developed using the identified risk factors as follows: 0.012 × miR-34a-5p + 0.012 × miR-122-5p − 0.001 × M30 + 2.642 × 1 (if mixed pattern) + 0.014 × 1 (if hepatocellular pattern) + 1.887. The AUC of the score was 0.86, with a sensitivity and specificity of 81%, better than the values of the single markers. Conclusions: Liver-specific miRNAs and K-18 could be promising serum biomarkers of DILI, especially when used in combination.